2001
DOI: 10.1037/0003-066x.56.11.977
|View full text |Cite
|
Sign up to set email alerts
|

Integrating gay, lesbian, and bisexual issues into mainstream psychology.

Abstract: Despite the growing clinical and research literature dealing with gay, lesbian, and bisexual (GLB) issues, mainstream psychology has tended to ignore much of the work that has been done in this area. This article illustrates how clinical and research writings on GLB issues continue to remain invisible to mainstream psychology in such areas as life span development and aging, teenage suicide, substance abuse, victimization and abuse, and family and couple relationships. It also deals with some of the determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 49 publications
0
49
0
1
Order By: Relevance
“…Both scientific literature and fieldwork have revealed that many psychotherapists continue to discriminate clients (Goldfried, 2001;Goldfried and Pachankis, 2007). This discrimination can happen in different ways, be it less visible, subtle or declared, for example by taking for granted the normative heterosexual orientation of their clients or prescribing sexual orientation conversion therapies.…”
Section: Homosexuality As a 'Mental Illness'mentioning
confidence: 99%
“…Both scientific literature and fieldwork have revealed that many psychotherapists continue to discriminate clients (Goldfried, 2001;Goldfried and Pachankis, 2007). This discrimination can happen in different ways, be it less visible, subtle or declared, for example by taking for granted the normative heterosexual orientation of their clients or prescribing sexual orientation conversion therapies.…”
Section: Homosexuality As a 'Mental Illness'mentioning
confidence: 99%
“…Indeed, LGB individuals have been viewed by some segments of society as antifamily (Goldfried & Goldfried, 2001;Strommen, 1993). When LGB individuals are portrayed as members of families both in research and in popular culture, the image is often one of an LGB individual estranged from his or her family of origin (Laird, 1998).…”
Section: Families Of Origin and Families Of Choicementioning
confidence: 99%
“…For instance, Goldfried (2001) discussed the insights that "mainstream" psychology can gain by focusing on such issues as LGB identity development, LGB close relationships, and families of choice, to name a few. Thus, possessing an awareness of the unique issues that LGB individuals bring to therapy not only decreases the negative effects of homophobia and heterocentrism on our LGB clients but also has the potential to increase our comprehensive understanding of human behavior.…”
Section: Working With Lgb Clientsmentioning
confidence: 99%
See 2 more Smart Citations